Cost savings from medication reviews in community pharmacies for nursing home residents in Estonia: a case study - Jürgen Jänese; Lauris Žēpers; Ágnes Lublóy (BMC, 2024)
Abstract Background The aim of this study is to assess the cost savings from medication reviews conducted for individuals living in nursing homes in Estonia. Medication reviews performed as part of the automated dose dispensing (ADD) service by community pharmacies might help identify suboptimal medicine regimens. Methods We use a case study approach to identify suboptimal use of medication in treatment plans and estimate the potential cost saving from medication reviews. To achieve this, we assess 101 treatment plans submitted for medication review by nursing homes in Estonia between 2021 and 2023. Additionally, we run OLS regressions to identify the most important determinants of medication cost savings. Results We estimate an average direct cost saving of €43.62 per patient per year, which corresponds to 8.27% of the average annual medication costs. If medication reviews were conducted for all elderly individuals over 75 years old who use six or more prescription medicines, nearly 2% of Estonia's pharmaceutical budget could be saved. Regression analysis indicates that the most significant contributors to these cost savings are suboptimal use of generics, incorrect dosages (too high), and the elimination of incorrect medications. Conclusions Our study suggests that annual medication reviews conducted as part of the ADD service might help reduce medication expenditure when offered to a wider public.